An alternative approach to transfer functions? Testing the performance of a functional trait-based model for testate amoeba - van Bellen, Simon (2017)
Transfer functions are now widely available to infer past environmental conditions from biotic assemblages. Existing transfer functions are based on species assemblages but an alternative is to characterize assemblages based on functional traits, characteristics of the organism which determine its fitness and performance. Here, we test the potential of trait-based transfer functions using testate amoeba functional traits to reconstruct peatland water-table depths. A total of seven functional traits with linkages to peat moisture content were identified and quantified as community weighted-means for each of 43 taxa in a training set from Tierra del Fuego, South America. Transfer functions based on (multiple) linear regression and partial least-squares were produced, validated using cross-validation and an independent test set, and applied to three core records. Trait-based models performed remarkably well. Model performance based on cross-validation and an independent test set was only marginally weaker than for models based on species and reconstructed down-core trends were extremely similar. Trait-based models offer considerable potential for paleoecological reconstruction particularly in no-analogue situations, where no species transfer function is available and for inexperienced analysts. The approach deserves further validation and testing for both testate amoebae and other groups of microfossils.